Influence of aging and surface treatments on the fatigue response of L-PBF manufactured steel parts - Bogojević, Nebojša; Ćirić-Kostić, Snežana; Sinđelić, Vladimir; Olmi, Giorgio; Croccolo, Dario (Advanced Technologies and Materials, 2024)
The processes of metal additive manufacturing (AM) offer advantages over traditional technologies, especially when it comes to producing parts with complex designs. Thanks to the flexibility in manufacturing processes and the relatively high speed of part production, AM technologies can now be found across various industries. A better understanding of the mechanical properties and fatigue behavior of metal parts is crucial for their successful integration in different sectors. Numerous factors play a key role in influencing the fatigue properties of metal parts produced through AM. This study investigates the impact of heat treatment and surface treatment on the fatigue behavior of components made from marginal steel (MS1) and stainless steel (PH1). After subjecting MS1 and PH1 steel to heat treatment, it is expected that the fatigue limits will increase compared to their original state. Additionally, experimental findings show that not only do surface treatments significantly affect fatigue strength when used alone, but also that changing the order of subsequent treatments can either enhance or diminish fatigue strength.